Odpowiedzi

2009-09-27T19:09:36+02:00
1.
x=y
5x-y=4

x=y
5*y-y=4

x=y
4y=4

x=y
y=1

2.
{y=2x+1
4x+y=13

y=2x+1
4x+2x+1=13

y=2x+1
6x=12

y=2x+1
x=2

y=5
x=2

3.
{5y-x=3
x=3-y

5y-3-y=3
x=3-y

4y=6
x=3-y

y=1,5
x=1,5

b).
2x-y=5
y=-5+2x

⅓ y=x-3
y=3x-9

3(x-y)=2x
3x-3y=2x
-3y=2x-3x
y=-2/3x + x

⅔x=¾y
3Y=8/3x
y=8/9x

4x+2y=1
y=1/2 - 2x

6x-⅔y gdzie tu jest znak "="?
2009-09-27T19:13:20+02:00
{x=y
5x-y=4

x=y
5x-x=4

x=y
x=1

x=1
y=1


y=2x+1
4x+y=13



2x-y=5
y=2x-5



y=2x+1
4x+2x+1=13

y=2x+1
6x=12

x=2
y=5

5y-x=3
x=3-y

x=5y-3
3-y=5y-3

x=5y-3
6=6y

y=1
x=2

⅓ y=x-3
y=3x-9

3(x-y)=2x
3x-3y=2x
x=3y
y=1/3x

⅔x=¾y
8x=9y
y=8/9x

4x+2y=1
2y=1-4x
y=0,5-2x

6x-⅔y=0
6x=⅔y
18x=2y
y=9x




Najlepsza Odpowiedź!
2009-09-27T19:17:13+02:00
1
x=y
5x-y=4
mamy x=y wiec podstawiaqmy
x=y
5*y-y=4
teraz
x=y
4y=4

x=y
y=1

czyli x=1
y=1

2.
y=2x+1
4x+y=13
podstawiamy
y=2x+1
4x+2x+1=13

y=2x+1
6x=12

y=2x+1
x=2
podstawiamy x=2
y=5
x=2


2x-y=5
y=-5+2x

⅓ y=x-3
y=3x-9

3(x-y)=2x
3x-3y=2x
-3y=2x-3x
y=-2/3x + x

⅔x=¾y /* 4
3y=8/3x /:3
y=8/9x

4x+2y=1
y=1/2 - 2x